Aplikasi Validasi e-KTP Berbasis Mobile Dengan Menerapkan Teknologi Optical Character Recognition - Sermana, Elsa Maharani; Kurniadi, Dede (Jurnal Algoritma, 2025)
The Electronic Identity Card (e-KTP) is an electronic identification document issued by the Indonesian government. The Department of Population and Civil Registration (Disdukcapil) is the government agency responsible for administering civil registration. Currently, a major issue in Garut Regency is the falsification of e-KTPs. The validation process is still performed manually, which is time-consuming and prone to errors. This study aims to design a mobile application that can validate the authenticity of e-KTPs using Optical Character Recognition (OCR) technology. The methodology used is the Rational Unified Process (RUP), which consists of four phases: Inception, Elaboration, Construction, and Transition. The application is built using the open-source OCR library Tesseract to recognize and extract text from e-KTP images. The results of this study show that the application can validate e-KTPs in real-time, although the accuracy is affected by lighting conditions during scanning. The implementation of OCR in this application successfully reduces manual errors and speeds up the e-KTP validation process. The contribution of this research lies in reducing the risk of identity fraud and improving the efficiency of administrative processes at Disdukcapil. The implication of this study is the potential for broader application of OCR in validating other types of identity documents.